2022
DOI: 10.12965/jer.2142718.359
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity interval training for chronic pain conditions: a narrative review

Abstract: Chronic pain is defined as pain that persists past the normal healing time. Physical activity and exercise programs are increasingly being promoted and used for a variety of chronic pain conditions. Evidence suggests that physical exercise is an intervention with few adverse events that may improve pain severity and physical function, thus improving the quality of life. High-intensity interval training (HIIT) has been shown to improve physical outcome measures and to decrease disorder-related disability in peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 82 publications
(112 reference statements)
0
7
0
Order By: Relevance
“…However, training professionals should be mindful that long-term daily HIIT training carries a potential risk of damage from overload. Prolonged HIIT eventually increases the likelihood of problems such as chronic pain syndrome and overuse syndrome, potentially leading to departure from team training [ 43 ]. Therefore, Smith et al mentioned HIIT as an effective short-term strategy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, training professionals should be mindful that long-term daily HIIT training carries a potential risk of damage from overload. Prolonged HIIT eventually increases the likelihood of problems such as chronic pain syndrome and overuse syndrome, potentially leading to departure from team training [ 43 ]. Therefore, Smith et al mentioned HIIT as an effective short-term strategy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIIT gained significant popularity worldwide as a fitness trend, and recent research has demonstrated its potential in reducing disability in people with different chronic musculoskeletal disorders such as fibromyalgia [36], axial spondylarthritis [61] and chronic non-specific low back pain [62][63][64][65]. In our review, we examined the effects of HIIT on knee OA as a standalone exercise modality or in comparison to training modalities with other exercise intensities such as MICT and LIT, or to CT. To the best of our knowledge, this is the first review that assessed the potential role of HIIT in mitigating symptoms associated with knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…HIIT has been proposed as a timeefficient form of exercise that may overcome motivational barriers associated with traditional moderate intensity training [33]. Several studies have demonstrated the effectiveness of HIIT on both healthy and pathological subjects [34][35][36]. Prior research shows that performing HIIT two to three times per week is sufficient to promote adherence and important physiological changes, such as improvements in cardiorespiratory health, body composition, and insulin sensitivity [37,38].…”
mentioning
confidence: 99%
“…Among its many benefits such as improving fat burning potential and AT in both healthy individuals and patients, including those with cardiovascular disease ( Wisløff et al, 2007 ), cancer ( Devin et al, 2016 ), or obesity ( Buckinx et al, 2018 ), it is also beneficial in the management of chronic pain. HIIT can be an important adjunct to conventional drug therapies and improve the quality of life of various populations ( Botta et al, 2022 ). It should be noted that most studies published to date have focused on older women who have already passed menopause or on elite athletes.…”
Section: Discussionmentioning
confidence: 99%